PENGAWASAN DAN PENEGAKAN HUKUM OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU TERHADAP TEMPAT PENAMPUNGAN SEMENTARA (TPS) ILEGAL DI KOTA PEKANBARU TAHUN 2023 - Yusuf, Nadya S.; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Illegal Temporary Shelters (TPS) are an unresolved problem in Pekanbaru City. The Department of Environment and Sanitation is a Government Agency tasked with managing waste, including illegal TPS in Pekanbaru City. This study aims to determine the form of supervision and law enforcement by the Department of Environment and Sanitation (DLHK) of Pekanbaru City in handling the problem of illegal TPS. This research uses a qualitative method, the theory used in presenting this research is the law enforcement theory of Aminudin Ilmar. Data collection techniques use interview and documentation methods. The type of data in this study is primary data, namely data obtained from research informants and secondary data obtained from related documents. The results of this study show that supervision by DLHK is divided directly and indirectly. Direct supervision is carried out by the DLHK Gakkum Unit assisted by Satpol PP. Indirect supervision of illegal TPSs is carried out in collaboration with third parties, namely business entities or waste management institutions. The form of DLHK law enforcement is government coercion, withdrawal of decisions, and imposition of fines or coercive money. Government coercion is in the form of confiscation of ID cards, demolition and confiscation of facilities. Withdrawal of decisions or revocation of permits is carried out on business entities that do not carry out their obligations as stipulated in Regional Regulation No. 8 of 2014. Meanwhile, coercive money is imposed on violators who are caught red-handed committing violations at illegal TPS locations. Keywords: DLHK, Supervision, Law Enforcement, Illegal TPS